2008
DOI: 10.1093/geront/48.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Change in Fruit and Vegetable Intake Over 24 Months in Older Adults: Results of the SENIOR Project Intervention

Abstract: The intervention was effective in increasing the intake of fruits and vegetables in older adults. Those who maintained their level of perceived intake as 5 or more servings per day consumed 2-4 servings per day more than those who failed to progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
70
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 34 publications
5
70
0
3
Order By: Relevance
“…As there is some evidence that stage of change is a predictor of fruit and vegetable intake (14) and that intervention strategies can be more successful when targeted to a particular stage of change (25)(26)(27)(28)(29)(30)(31)(32)35,37,38,52) , there are a number of key learnings from the present study that lend weight to the argument for focusing predominantly on vegetable consumption.…”
Section: Stage Of Changementioning
confidence: 64%
See 2 more Smart Citations
“…As there is some evidence that stage of change is a predictor of fruit and vegetable intake (14) and that intervention strategies can be more successful when targeted to a particular stage of change (25)(26)(27)(28)(29)(30)(31)(32)35,37,38,52) , there are a number of key learnings from the present study that lend weight to the argument for focusing predominantly on vegetable consumption.…”
Section: Stage Of Changementioning
confidence: 64%
“…It shapes beliefs that in turn shape action' (23) . The transtheoretical model of behaviour change or 'stages of change' model has been used to inform the planning of many health-related interventions (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) . The model suggests that individuals can be categorised into different stages of readiness to change health behaviours including pre-contemplation, contemplation, preparation, action and maintenance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, interventions on changing FV consumption may aim to reduce the importance of negative beliefs arising from behavior change (20). The efficacy of stagetailored nutrition education has been demonstrated in several studies though there were some differences (9,36,37,38). Although some studies have failed to find any significant pros factor for predicting the stages of change (20,39), in the present study, we found that maintaining an ideal weight, being healthy, and inducing a variation in the diet are all among the significant benefits of FV consumption.…”
Section: Discussionmentioning
confidence: 99%
“…In two qualitative studies, Devine et al (21) and Dye and Cason (22) also report discussion of the importance of wanting to change and the benefits of medical advice and social support to aid dietary changes. Interventions focusing specifically on individuals who are ready and willing to change also typically demonstrate greater success compared to interventions that are more general (29,35,36) . The findings of the present study suggest that f 1 v intake may be improved in the older female population by increasing willingness to change.…”
Section: Discussionmentioning
confidence: 99%